Does the public antiretroviral treatment programme meet patients' needs? A study at four hospitals in eThekwini, KwaZulu-Natal, South Africa - Delarise M. Mulqueeny; Myra Taylor (AOSIS, 2019)
Background: Patients play a major role in the success of any antiretroviral treatment (ART) programme. Hence, their needs should be articulated on a regular basis for interventional processes to promote adherence, retention and quality care. Aim: This study investigated whether patients' needs were being met, described which needs were met, which were not and how such needs could be met. Setting: The study took place at four ART clinics in eThekwini district public hospitals. Methods: This study formed part of a larger study that utilised a sequential mixed-methods design. However, only the qualitative component is documented herein. Twelve HIV-infected patients engaged in in-depth interviews (three patients from each of the four hospitals). A socio-ecological framework divided responses into four categories, namely, the individual, interpersonal, institutional and policy. Each category presented (1) patients' needs that are being met, (2) needs that are not being met, (3) recommendations on how they can be met and (4) researchers' observations. Results: All 12 patients reported that all their needs were not being met. They further shared their met needs, unmet needs and made recommendations for meeting their unmet needs. These needs varied per antiretroviral clinic because of unique processes at each institution. Conclusion: To adequately address the needs of HIV-infected patients, it is imperative for all stakeholders involved in the public ART programme to gain an understanding of what constitutes 'patients' needs'. The results reflect patients' willingness to be involved in their care, treatment and interventional strategies to adequately meet their needs.